The prison of love : romance, translation, and the book in the sixteenth century - Francomano, Emily C. (Studies in book and print culture., 2018)
The Spanish romance Cárcel de amor blossomed into a transnational and multilingual phenomenon that captivated audiences throughout Europe at a time when literacy was expanding and print production was changing the nature of reading, writing, and of literature itself. In The Prison of Love, Emily Francomano offers the first comparative study of this sixteenth-century work as a transcultural, humanist fiction. Blending literary analysis and book history, Francomano provides us with the richly textured history of the translations, material books, and artefacts that make this tale of love, letters, and courtly intrigue an invaluable prism through which the multifaceted world of sixteenth-century literary and book cultures are refracted.